Printed field effect transistors - Foo, Suan Wood. (2009)
This final year project will explore the feasibility of fabricating inkjet printed devices, specifically Organic Field Effect Transistors (OFETs). This study will report important processing conditions, design fabrications, methodology and materials selection, which have profound effect on the electrical performance of printed devices. This project focuses on the use of inkjet print technology to fabricate low cost organic devices.